An Index Approach to Early Specialization Measurement: An Exploratory Study - Downing, Charlotte; Redelius, Karin; Nordin-Bates, Sanna M. (Frontiers in Psychology, 2020)
The methodological underpinnings of studies into early specialization have recently been critiqued. Previous researchers have commented on the variety of, and over-simplified, methods used to capture early specialization. This exploratory study, therefore, suggests a new direction for how early specialization can be conceptualised and measured. We aim to create an index approach whereby early specialization is measured as a continuous variable, in line with commonly used definitions. The continuous variable for degrees of early specialization is calculated from a questionnaire which captures the four key components of early specialization; 1) intensity, 2) year-round training, 3) single sport, and 4) commencing age 12 or younger. The proposed index approach is illustrated in a sample of 290 Swedish aesthetic performers aged 12-20 years (M = 15.88), whose descriptive statistics are used to discuss the suitability and usability of the measure. The proposed index approach functions as a guideline to future researchers. We hope that introducing a new index approach we will encourage further discussion around the measurement of early specialization. Additionally, we hope to pave the way for future research to explore more complex research questions.